Effects of paracetamol on the polychaete Hediste diversicolor: occurrence of oxidative stress, cyclooxygenase inhibition and behavioural alterations - Nogueira, Ana Filipa (2022)
Pharmaceuticals are significant environmental stressors, since they are utilized around the world; they are usually released in to the aquatic system without adequate treatment and several non-target species can be harmed because of their intrinsic properties. Paracetamol is one of the most widely prescribed analgesics in human medical care. Consequently, this compound is systematically reported to occur in the wild, where it may exert toxic effects on non-target species, which are mostly uncharacterized so far. The objective of the present work was to assess the acute (control, 5, 25, 125, 625 and 3125 μg/L) and chronic (control, 5, 10, 20, 40 and 80 μg/L) effects of paracetamol on behavioural endpoints, as well as on selected oxidative stress biomarkers [superoxide dismutase (SOD), glutathione peroxidase (GPx), glutathione reductase (GRed)] and the anti-inflammatory activity biomarker cyclooxygenase (COX), in the polychaete Hediste diversicolor (Annelida: Polychaeta). Exposure to paracetamol caused effects on behavioural traits, with increased burrowing time (96 h) and hypoactivity (28 days). In addition, exposure to paracetamol resulted also in significant increases of SOD activity, but only for intermediate levels of exposure, but for both acute and chronic exposures. Both forms of GPx had their activities significantly increased, especially after chronic exposure. Acutely exposed organisms had their GRed significantly decreased, while chronically exposed worms had their GRed activity augmented only for the lowest tested concentrations. Effects were also observed in terms of COX activity, showing that paracetamol absorption occurred and caused an inhibition of COX activity in both exposure regimes. It is possible to conclude that the exposure to concentrations of paracetamol close to the ones in the environment may be deleterious to marine ecosystems, endangering marine life by changing their overall redox balance, and the biochemical control of inflammatory intermediaries. Behaviour was also modified and the burrowing capacity was adversely affected. This set of effects clearly demonstrate that paracetamol exposure, under realistic conditions, it not exempt of adverse effects on marine invertebrates, such as polychaetes.